Immediate and partial neural dysfunction after thyroid and parathyroid surgery: Need for recognition, laryngeal exam, and early treatment. Issue 12 (21st September 2020) - Dhillon, Vaninder K.; Randolph, Gregory W.; Stack, Brendan C.; Lindeman, Brenessa; Bloom, Gary; Sinclair, Catherine F.; Woodson, Gayle; Brooks, Jennifer A.; Childs, Lesley F.; Esfandiari, Nazanene H.; Evangelista, Lisa; Guardiani, Elizabeth; et al.
Abstract: Background: Laryngeal dysfunction after thyroid and parathyroid surgery requires early recognition and a standardized approach for patients that present with voice, swallowing, and breathing issues. The Endocrine Committee of the American Head and Neck Society (AHNS) convened a panel to define the terms "immediate vocal fold paralysis" and "partial neural dysfunction" and to provide clinical consensus statements based on review of the literature, integrated with expert opinion of the group. Methods: A multidisciplinary expert panel constructed the manuscript and recommendations for laryngeal dysfunction after thyroid and parathyroid surgery. A meta‐analysis was performed using the literature and published guidelines. Consensus was achieved using polling and a modified Delphi approach. Results: Twenty‐two panelists achieved consensus on five statements regarding the role of early identification and standardization of evaluation for patients with "immediate vocal fold paralysis" and "partial neural dysfunction" after thyroid and parathyroid surgery. Conclusion: After endorsement by the AHNS Endocrine Section and Quality of Care Committee, it received final approval from the AHNS Council.